Surgical Treatment of Plantar Fasciitis After failure of Conservative Treatment - Dr. Ammar khayoon Jarallah Alkinany; Dr. Burhanadeen Abdulazez Jabbar Alabudi; Dr. Hassan Ali Shamkhie Aljanabi (Zien Journals, 2023)
Plantar fasciitis is a common problem faced almost daily in our orthopedic clinic, and it is not easy to satisfy patients with a curative treatment in a short period of time; it is characterized by deep pain in the plantar aspect of the heel, particularly on arising from bed, although the pain often subsides after few steps, in some patients the pain will persist for a long period. Aim of the study: To evaluate the result of surgical treatment in cases of plantar fasciitis which are not respond to conservative treatment. Methods: Prospective study was conducted at the Department of Orthopedic Surgery in Al-Kadhemiyah Teaching Hospital from November 2010 to May 2012 to evaluate 50 patients com¬plaining of inferior heel pain. There were 30 females and 20 males; the main presenting symptoms were pain on the inferno-medial aspect of the heel exacerbating by prolongs weight-bearing and in the morning following sleep. The age of the patients is 23-58 years. Bilateral heel pain presented in 10 patients in our series; therefore, the overall number of heels treated in our series was 60 heels. All of the patients were treated first conservatively by rest, anti-inflammatory drugs, and local corticosteroid injection. 13 patients showed no response, so we advised them for surgery; 12 patients out of 13 accepted surgery and were treated by plantar fascial release. Patients with systemic diseases had been excluded from our study. Results: Regarding treatment, 37 patients (74%) respond to conservative treatment, while 13 patients (26%) had no response to conservative treatment. Therefore they were advised to undergo surgery, and 12 of them accepted surgery. Nine patients (75%) undergoing surgery had a good result (pain-free) 17% of patients undergoing surgery in our study showed fair results (pain after heavy exercise), while 8% showed poor results (persistent pain). Per-operative drilling of calcaneum showed to be effective in post-operative heel pain relieve, which may be due to reduced intra-osseous pressure. Regarding complications, 6% showed superficial wound infection, which was treated conservatively by rest and antibiotics for seven days. Post-operative back slab for two weeks is important to decrease post-operative pain and to facilitate soft tissue healing
Keywords: orthopedic; Plantar fasciitis